Examining the role of social factors in the utilization of preventive cardiovascular clinical services: An analysis using Andersen’s behavioral health model - Sultan Saad Alamri; Abuobieda Khogali Abdalrouf; Fahad Mustafa Alnouri; Ammar Hamid Suliman (PLoS ONE, 2026)
Background Cardiovascular disease (CVD) remains the leading cause of mortality in Saudi Arabia, mainly influenced by multiple lifestyle risk factors. Addressing this challenge requires a comprehensive evaluation of preventive services, particularly Preventive Cardiovascular Clinical Services (PCCS), which are essential for early detection and management. Hence, studying the utilization of PCCS is crucial to assess uptake and inform strategies to combat CVD burden. Methods A survey-based cross-sectional study was conducted at the largest primary healthcare center under the Armed Forces Healthcare Services (AFHS) in Riyadh, Saudi Arabia. We surveyed 384 respondents to assess predisposing, enabling, and need factors that influence the utilization of nine PCCS using Andersen’s Behavioral Model of Health Services Use. Descriptive statistics and logistic regression models were employed to explore predictors of service utilization. Results The study revealed a notably high prevalence of both positive family history (90%) and self-reported diagnosis (53%) of CVD among participants, highlighting significant disparities in the utilization of PCCS across different service types and participant characteristics. Predisposing factors, including sex, age, parenthood, and educational attainment, consistently influenced the utilization of various PCCS. Sex-specific disparities were observed, with female individuals engaging in more PCCS, while gaps persisted in services such as smoking-cessation counseling. Personal and organizational enabling factors, including vehicle ownership and proximity to the nearest primary healthcare center, were crucial in facilitating access to healthcare. Finally, need factors, such as family history of CVD, the presence of CVD risk factors, and perceived health status, strongly influenced individuals’ motivations for seeking PCCS. Conclusion The complex intertwining of multiple personal, structural, and contextual factors further underscores the need to enhance PCCS user experience by designing, implementing, and monitoring targeted interventions, particularly for high-risk groups, based on their predisposing, enabling, and need profiles.